Aeroelasticity - Bisplinghoff, Raymond L. (Dover Publications, 1996)
Highly regarded resource deals with practical aspects of aeroelasticity as well as underlying aerodynamic and structural tools. Topics include compressible flow, flutter, deformation of structures, aeroelastic model theory, model design and construction, testing techniques and much more. Many numerical examples. Appendices. References. Over 300 illustrations. 1955 edition.
Corrected republication of the work originally published: Cambridge, Mass. : Addison-Wesley, 1955.
Keywords: Aeroelasticity.; elektronické knihy; electronic books